The Kids and Teens at School (KiTeS) Framework: An Inclusive Bioecological Systems Approach to Understanding School Absenteeism and School Attendance Problems - Melvin, Glenn A.; Heyne, David; Gray, Kylie M.; Hastings, Richard P.; Totsika, Vaso; Tonge, Bruce J.; Freeman, Mina Mirjana (Frontiers in Education, 2019)
The Warnock report was instrumental in highlighting the need to individualise educational supports for children and adolescents with disabilities in order to foster optimal educational outcomes. When children and adolescents are absent from school or experience school attendance problems, their educational outcomes are jeopardized as is their social and emotional development. Proximal and distal individual, parental, familial, and environmental factors have been implicated in the development and maintenance of absenteeism and school attendance problems. The complex interaction amongst these factors calls for a multifactorial approach to understanding the development of school attendance problems. The current paper presents a bioecological systems framework for examining risk factors for school absenteeism and school attendance problems among all school-aged students. The framework aims to identify the concurrent influence of factors across multiple contexts such as home, school, and society. We propose candidate factors of particular relevance to school attendance problems in school age students, and organise them in a bioecological systems framework, known as the Kids and Teens at School (KiTeS) framework. The framework is inclusive of students with and without disabilities and provides a guiding structure to researchers aiming to improve understanding of the factors that influence absenteeism and school attendance problems.